HUBUNGAN KOMUNIKASI TERAPEUTIK DENGAN KECEMASAN PASIEN PRE OPERASI SECTIO CAESAREA (SC) DI RSIA UMMU HANI PURBALINGGA - Riana Retno Kusmianasari; Pramesti Dewi; Danang Tri Yudono (Bajang Institute, 2022)
Sectio caesarea (SC) is a delivery that requires surgery. Surgery will cause anxiety. Anxiety that occurs in patients can be overcome by nurses conveying clear information to patients and their families about the patient's illness, the cause of the disease, the consequences of the disease and what actions will be given to the patient. The purpose of this study was to determine the relationship between nurse therapeutic communication and anxiety levels of preoperative sectio caesarea (SC) patients at RSIA Ummu Hani Purbalingga. The survey research design is a correlational study using a cross sectional time approach. The sample in this study were patients with SC surgery at RSIA Ummu Hani Purbalingga as many as 53 respondents with consecutive sampling technique. The research instrument used a therapeutic communication questionnaire and the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire with data analysis using spearman rank. The results showed that nurses' therapeutic communication was mostly in the good category (67.9%), the anxiety level of preoperative sectio caesarea (SC) patients was mostly in the mild and moderate category (43.4%). There is a relationship between nurse's therapeutic communication with the anxiety level of preoperative sectio caesarea (SC) patients at RSIA Ummu Hani Purbalingga with a p value of 0.001 with a rho value of -0.454.